Impact of education on anemia in pregnant women attending Bandung community health centers: knowledge, therapy adherence, hemoglobin, and iron intake - Zazuli, Zulfan; Furqani, Winda Haniva; Putri, Suci Utami Ayungga (Faculty of Pharmacy, Universitas Pancasila, 2024)
Anemia in pregnant women poses risks to maternal and infant health. Iron supplementation therapy (IST) adherence and adequate dietary iron intake are crucial for maintaining normal hemoglobin (Hb) levels. This study investigates the impact of education on iron deficiency anemia (IDA) knowledge, IST adherence, iron intake, and Hb levels in pregnant women. A pre-post test study was conducted at Padasuka and Pagarsih Community Health Centers in Bandung. Questionnaires measuring IDA knowledge, Brief Medication Questionnaire (BMQ) for IST adherence, and Food Frequency Questionnaire (FFQ) for iron intake were utilized. This study included a total of 88 pregnant women. The majority of the participants were aged 26-35 years (55.7%), had normal BMI values (45.4%), and exhibited normal blood pressure (60.2%). Additionally, 89.8% had no history of anemia, 90.9% had no other medical history, 92% reported having a good appetite, and 97.7% did not smoke. Education significantly improved IDA knowledge (p = 0.011), IST adherence (p = 0.006), iron intake (p = 0.001), and Hb levels (p = 0.011). Strong positive correlations were found between knowledge of IDA in pregnant women and adherence to IST (r = 0.957; p<0.001), knowledge and Fe intake (r = 0.972; p<0.001), knowledge and Hb levels (r = 0.988; p<0.001), adherence to IST and Fe intake (r = 0.933; p<0.001), adherence to IST and Hb levels (r = 0.948; p<0.001), as well as Fe intake and Hb levels (r = 0.978; p<0.001). Enhanced knowledge, IST adherence, and iron intake may mitigate anemia risks in pregnant women.